Telepathology in intraoperative frozen section consultation of breast cancer sentinel node biopsy in Fukushima, Japan following the 2011 triple disaster: diagnostic accuracy and required time during the early implementation phase - Hiroaki Kawakami; Akihiko Ozaki; Yudai Kaneda; Shigeyuki Asano; Kouki Inai; Shinichi Hirooka; Ayumi Katoono; Riko Takagi; Makoto Kosaka; Anju Murayama; Toyoaki Sawano; Yasuteru Shimamura; et al. (James Cook University, 2023)
In breast cancer surgery, some medical facilities lack the necessary resources to conduct sentinel lymph node biopsy and its intraoperative frozen section consultation. In the coastal rural area of Fukushima, Japan, which has suffered from physician undersupply following the 2011 triple disaster of earthquake, tsunami and nuclear disaster, we explored the feasibility of telepathology by evaluating the diagnostic accuracy in remote intraoperative frozen section consultation of sentinel lymph node biopsy and its required time. Although examination time has room for improvement, telepathology can be one possible solution in resource-limited areas.